45 years after the discovery of human polyomaviruses BK and JC: Time to speed up the understanding of associated diseases and treatment approaches. (4th March 2017) - Barth, Heidi; Solis, Morgane; Lepiller, Quentin; Sueur, Charlotte; Soulier, Eric; Caillard, Sophie; Stoll-Keller, Françoise; Fafi-Kremer, Samira
Abstract: Nearly 45 years after the discovery of the first two human polyomaviruses BK and JC, their life-long persistence and mechanisms of pathogenesis remain poorly understood and efficient antiviral treatments are severely lacking. In this review, we sought to provide an update on recent advances in understanding the life cycle of these two viruses, particularly focusing on their interaction with the host immune system and pathogenesis. We have also discussed novel treatment approaches and highlighted areas of future research.